Joan of Arc in New Age Spirituality - Kavan, Heather (Relegere, 2013)
This paper explores New Age interpretations of Joan of Arc, both as a fifteenth-century woman and as a spiritual being. The central focus is on messages believed to be from Joan (or “Jeanne”), channeled by Starla Hinman. I analyze the content and impact of these messages, and conclude that a new archetype of Joan has emerged—as a woman of the future who can positively transform the world. Additionally, I discuss five ways in which spiritual seekers perceive Joan today: as a mystic, an ascended master, a personification of the divine feminine, a torch-bearer of the Holy Grail, and the embodiment of Michaelic and Marian essences